POST-COVID NEUROLOGICAL COMPLICATIONS: MECHANISMS, CLINICAL MANIFESTATIONS, AND TREATMENT STRATEGIES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
The coronavirus disease 2019 (COVID-19) pandemic has resulted in a substantial global health burden, not only due to acute infection but also because of persistent post-infectious complications. Among these, neurological manifestations have emerged as a major concern, affecting both central and peripheral nervous systems. Post-COVID neurological complications range from mild cognitive impairment and headache to severe conditions such as stroke, encephalitis, and peripheral neuropathies. This article reviews current evidence on the underlying mechanisms of post-COVID neurological involvement, including neuroinflammation, immune dysregulation, endothelial dysfunction, and direct or indirect viral effects. Clinical manifestations, diagnostic approaches, and current treatment strategies are discussed, along with future perspectives for long-term management and rehabilitation.